2017
DOI: 10.1016/j.apsusc.2017.01.178
|View full text |Cite
|
Sign up to set email alerts
|

A new insight into the interfacial mechanisms of the tribofilm formed by zinc dialkyl dithiophosphate

Abstract: Understanding the true interfacial mechanisms involved in the growth of tribofilms generated by Zinc Dialkyl Dithiophosphate (ZDDP) is important because it is the most widely used antiwear additive and there is legislative pressure to find efficient environmentally-friendly replacements. The main focus of this study is to investigate the durability of the ZDDP tribofilm and correlate it to the chemical and physical properties of the glassy polyphosphates.A novel experimental method has been developed to study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 56 publications
6
43
0
Order By: Relevance
“…Parsaeian et al [12,16] found that water can affect the performance of ZDDP by altering the polyphosphates chain length. This effect manifests itself in the formation of shorter polyphosphate chain at higher levels of relative humidity [16,23]. The results are in a good agreement with the study done by Nedelcu et al [24].…”
Section: Effect Of Water On Lubricationsupporting
confidence: 82%
“…Parsaeian et al [12,16] found that water can affect the performance of ZDDP by altering the polyphosphates chain length. This effect manifests itself in the formation of shorter polyphosphate chain at higher levels of relative humidity [16,23]. The results are in a good agreement with the study done by Nedelcu et al [24].…”
Section: Effect Of Water On Lubricationsupporting
confidence: 82%
“…One way to assess the durability of a ZDDP tribofilm is to monitor changes in ZDDP tribofilm thickness after the replacement of a ZDDP-containing oil by a ZDDP-free oil [1][2][3]. Fujita et al [1] measured the growth of a thick ZDDP tribofilm in rolling-sliding contact using optical interferometry and then the effect on this pre-formed tribofilm of replacing the ZDDP solution by base oil.…”
Section: Introductionmentioning
confidence: 99%
“…This picture has, however, recently become more complicated since Parsaeian et al [3] have shown that the durability of a ZDDP tribofilm appears to depend on how long it has been rubbed. Like Fujita et al, they found that if ZDDP solution was replaced by base oil after prolonged rubbing, the tribofilm was not significantly removed during further rubbing and was thus durable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One is that the ZDDP tribofilm formation stage 1 was quite long in this work, at 3-h rubbing. A number of studies have found that ZDDP tribofilms gradually transform from polyphosphate to short-chain phosphate during extended rubbing [42,43] and it is thus quite likely that most of the tribofilm formed in the current study was, in fact depolymerised orthophosphate. Concerning the immediate surface where polyphosphate might be expected to be most likely to be present, this may have been removed by cleaning.…”
Section: Discussionmentioning
confidence: 80%